2012
DOI: 10.1242/jeb.071704
|View full text |Cite
|
Sign up to set email alerts
|

The neural mechanisms of antennal positioning in flying moths

Abstract: SUMMARYIn diverse insects, the forward positioning of the antenna is often among the first behavioral indicators of the onset of flight. This behavior may be important for the proper acquisition of the mechanosensory and olfactory inputs by the antennae during flight. Here, we describe the neural mechanisms of antennal positioning in hawk moths from behavioral, neuroanatomical and neurophysiological perspectives. The behavioral experiments indicated that a set of sensory bristles called Böhmʼs bristles (or hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 44 publications
(63 reference statements)
7
79
0
1
Order By: Relevance
“…Latencies to firing shift were significantly higher (P<0.01; Fig. 2C) than those reported for intrinsic muscle responses to stimulation of the Böhm's bristles (Krishnan et al, 2012). Additionally, the response latencies to ipsilateral and contralateral visual stimulation were not significantly different from each other.…”
Section: Visual Input To the Antennal Muscles Is Slower Than Mechanosmentioning
confidence: 52%
See 4 more Smart Citations
“…Latencies to firing shift were significantly higher (P<0.01; Fig. 2C) than those reported for intrinsic muscle responses to stimulation of the Böhm's bristles (Krishnan et al, 2012). Additionally, the response latencies to ipsilateral and contralateral visual stimulation were not significantly different from each other.…”
Section: Visual Input To the Antennal Muscles Is Slower Than Mechanosmentioning
confidence: 52%
“…1). This also contrasts with the mechanosensory input to the same muscles, which is thought to be ipsilaterally confined (Krishnan et al, 2012). In addition, we also observed that the latencies of muscle responses to contralateral and ipsilateral visual stimulation were similar ( Fig.…”
Section: Bilateral Motion-sensitive Visual Input To the Antennal Musclesmentioning
confidence: 55%
See 3 more Smart Citations